COULD SACREDNESS CONTRIBUTE TO FOREST CONSERVATION IN AFRICAN URBAN AREAS ? - HOUNGBO, NOUNAGNON EMILE; DJEGO, Gaudence Julien; OREKAN, VINCENT OLADOKOUN AGNILA.; LOUGBEGNON, OLOU TOUSSAINT; MONGBO, ROCH LAMBERT; SINSIN, AUGUSTIN BRICE (My University, 2013)
Attention is presently paid to forest conservation because of its potential for the sequestration of carbon. More than rural forest, urban forest is of greater utility because of it can serve as a natural low cost laboratory for pedagogic activities of several schools. Unfortunately those forests are regressing in Benin. The objective of this study is to analyze whether sacredness could help reverse this situation in State forest reserve. It focused on two urban forests : the State forest reserve of Abomey (Abomey District) in the centre of Benin, and the State forest reserve of Kilir (Djougou District) in the northern Benin. The information was collected through a literature review on the administrative status of these forests, a mapping and enumeration of forest species, participant observation of the pressure on the forests, traditional authority interview and focus groups analysis with stakeholders of both forests. The investigation revealed that the size of the two forest decreased drastically, while each of the remaining parts sheltered a sacred space. From respectively a size of 173 ha in 1941 and a size of 50 ha in 1949, 43.4 % of the Abomey forest and 70 % of the Kilir forest are occupied illegally. Sacred spaces were completely preserved through time, suggesting that a sufficient recovery of sacred powers could facilitate the sustainable management of urban State forest reserve.
Keywords: Sacredness; Urban Forests; Conservation; Benin.